2020
DOI: 10.21203/rs.3.rs-65350/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Influence of trivalent rare earth (Dy3+) ions substitution on the structural, magnetic and dielectric properties of nanosized Ni0.6Cd0.4DyxFe2‒xO4 ferrites

Abstract: In the present work, Ni0.6Cd0.4DyxFe2‒xO4 (x = 0.0, 0.05, 0.10, 0.15 and 0.20) nanoparticles (NPs) were synthesized by using sol-gel auto combustion method. The structural characterization was performed by XRD, FTIR, SEM, TEM and EDS analyses. XRD patterns confirmed that the pure and dysprosium substituted Ni-Cd ferrites are in single phase spinel structures, while a trace of DyFeO3 appears as a minor phase for higher concentrations (x = 0.10, 0.15 and 0.20). The Debye‒Scherrer’s method and Williamson-Hall (W-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…In general, the absorption band (ν 1 ) which appears in the range of 500-600 cm −1 is attributed to the intrinsic vibration of tetrahedral metal-oxygen bond, while the lower absorption band (ν 2 ) appeared in the range of 400-480 cm −1 is assigned to the octahedral metal-oxygen bond. These two bands are considered to be a typical of spinel ferrite structure and confirm the formation of spinel ferrite [1,27,42]. These FTIR results are in compliance with the result obtained from the XRD analysis.…”
Section: Ftir Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…In general, the absorption band (ν 1 ) which appears in the range of 500-600 cm −1 is attributed to the intrinsic vibration of tetrahedral metal-oxygen bond, while the lower absorption band (ν 2 ) appeared in the range of 400-480 cm −1 is assigned to the octahedral metal-oxygen bond. These two bands are considered to be a typical of spinel ferrite structure and confirm the formation of spinel ferrite [1,27,42]. These FTIR results are in compliance with the result obtained from the XRD analysis.…”
Section: Ftir Analysissupporting
confidence: 88%
“…Ionic radii of elements have an impact on lattice constant [1]. As a result, the exchange of larger La 3+ ions (ionic radii of 1.6061 Å) in the arrangement of the smaller Fe 3+ ions (0.645 Å) on octahedral B-site would cause the expansion of unit cell dimensions and resulting in increase in the lattice constants [42,48]. Using the cell constant value, the unit cell volumes of NZF and LNZF were calculated by using the equation (3) and which were found to be 571.8 Å 3 and 592.702 Å 3 respectively.…”
Section: Xrd Analysismentioning
confidence: 99%
“…The properties of MgFe2O4 can be modified by doping of divalent or trivalent ions. In literature many researchers have reported that the doping of rare earth metals in ferrites may alter the intrinsic properties of ferrites [11].…”
Section: Introductionmentioning
confidence: 99%